Study of Covariates’ Effects in the Presence of Neighbor Effects : An Informative Review - Sapam, Sobita; Sinha, Bikas K; Meitei, KK Singh (International Journal of Statistical Sciences, 2024)
With reference to a Gauss-Markov Model, Analysis of Covariance (ANCOVA) is a standard exercise in the study of differential treatment effects in the presence of covariates. Again in the presence of ‘Neighbor Effects’, we carry out necessary data analysis in a routine manner. In this paper we present a review of this area of research, encompassing both covariates’ effects and neighbor effects. International Journal of Statistical Sciences, Vol.24(1), March, 2024, pp 65-73